2018
DOI: 10.2196/10091
|View full text |Cite
|
Sign up to set email alerts
|

Early Psychosis Service User Views on Digital Technology: Qualitative Analysis

Abstract: BackgroundDigital technology has the potential to improve outcomes for people with psychosis. However, to date, research has largely ignored service user views on digital health interventions (DHIs).ObjectiveThe objective of our study was to explore early psychosis service users’ subjective views on DHIs.MethodsFramework analysis was undertaken with data obtained from 21 semistructured interviews with people registered with early intervention for psychosis services. Robust measures were used to develop a stabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 39 publications
(46 reference statements)
4
92
0
Order By: Relevance
“…Thus, as in previous studies with both patients and staff, participants in the current study suggested that self-monitoring apps should enhance rather than replace face-to-face appointments [30,57]. Nevertheless, as participants in a recent study hypothesized [42], some found an app more accessible than mental health staff, reporting that they are more open about their symptoms on an app, they can complete it at points when they are unwilling to speak to someone, it is more frequent than their usual contact with a clinician and it removes the feeling of inconveniencing someone to report symptom increases. Furthermore, several participants with low symptoms described the app in positive, anthropomorphic terms (e.g.…”
Section: Principal Resultssupporting
confidence: 50%
See 3 more Smart Citations
“…Thus, as in previous studies with both patients and staff, participants in the current study suggested that self-monitoring apps should enhance rather than replace face-to-face appointments [30,57]. Nevertheless, as participants in a recent study hypothesized [42], some found an app more accessible than mental health staff, reporting that they are more open about their symptoms on an app, they can complete it at points when they are unwilling to speak to someone, it is more frequent than their usual contact with a clinician and it removes the feeling of inconveniencing someone to report symptom increases. Furthermore, several participants with low symptoms described the app in positive, anthropomorphic terms (e.g.…”
Section: Principal Resultssupporting
confidence: 50%
“…Other key barriers which could be addressed to increase app engagement included lack of smartphone experience, skepticism regarding the app, the study policy to not use the app whilst abroad and lack of literacy. Although the latter was also reported as a potential barrier by a third of participants in a recent qualitative study, they nevertheless found smartphones more accessible than paper-based alternatives [42].…”
Section: Principal Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Participants believed that entering data on a DHI in the absence of any clinician involvement may be meaningless. Therefore, participants were willing to grant the care team access to their data, but had mixed views about whether this access should be automatic or user-initiated.Traditionally, symptom monitoring approaches tend to involve the automatic transfer of symptom information [48]; however, these findings suggest service users should have control over information transfer, which echoes views expressed by staff [49] and individuals with bipolar disorder [50] and first episode psychosis [51]. Concerns over third party access were also expressed and may be a barrier to DHI uptake by people with severe mental health problems.…”
Section: Discussionmentioning
confidence: 99%